Pemisahan dan Karakterisasi Senyawa dari Ekstrak Etanol Umbi Talas Safira (Colocasia esculenta Schott var. antiquorum) - Karla Fransiska; Burhanuddin Taebe; Risfah Yulianty; Lukman Muslimin (Jurnal Farmasi dan Ilmu Pengobatan, 2019)
Research on the separation and characterization of chemical compounds from taro tuber (Colocasia esculenta Schott var. antiquorum) has been done. The maceration results of 850.00 g simplicial with 70 % ethanol solvent obtained 102.16 g brown viscous extract. The result of chemical components identification showed that the ethanol extract of taro tuber was positive for alkaloids, flavonoids, and terpenoids. Separation and purification of the ethanol extract were done by a liquid-liquid partition, thin layer chromatography and two-dimensional chromatography with a combination of n-hexane and ethyl acetate (2:8) as mobile phase. We found 4 bands (I-IV) with maximum wavelength were 407.0, 268.50, 253.00, and 209.50 nm. The presence of absorption at a wavelength of 268.50 nm and 253.00 nm indicating the presence of a class of flavonoids. The infrared spectrum showed that the isolates had typical groups such as O-H, C=O, C-C, C-O, and C=C.